Child Protection, Disability and Obstetric Violence: Three Case Studies from Iceland - James Gordon Rice; Helga Baldvins Bjargardóttir; Hanna Björg Sigurjónsdóttir (International Journal of Environmental Research and Public Health, 2020)
This contribution is a collective re-analysis of three research projects in Iceland focused on parenting with a disability which draws upon data spanning a twenty-year period. The core purpose of these projects is to understand why parents with primarily intellectual disabilities encounter such difficulties with the child protection system. Our aim with this contribution is to identify, through a longitudinal and comparative framework, why these difficulties persist despite a changing disability rights environment. A case study methodology has been employed highlighting three cases, one from each research project, which focus narrowly on disabled parents’ struggles with the child protection system in the context of the maternity ward. The findings, framed in the concept of structural violence, indicate poor working practices on the part of healthcare and child protection, a lack of trust, and that context is still ignored in favour of disability as the explanatory framework for the perceived inadequacies of the parents. We contend that child protection authorities continue to remain out of step with developments in disability and human rights. The contribution concludes to make a case as to why the concept of obstetric violence is a useful framework for criticism and advocacy work in this area.